Smart Room System with Remote Access Using MQTT - Merunei, Nick Cassidy; Chew Chang Choon , (Evolution in Electrical and Electronic Engineering, 2022)
The smart building has become increasingly popular, especially among university and technology-based companies, as it offers greater efficiency in terms of energy management, and harnesses the power of facilities information that leads to better decision-making and more streamlined operations. From a room with a smart whiteboard to a room that automatically turns on its light for any visitor, it is clear that everything can be achieved with technology. This project aims to develop a smart room that is based on a webserver. Instead of using an application to monitor the room. This can be done by using the DHT11 temperature-humidity sensor, as this sensor can measure a range of temperature from 0oC to 50oC. In contrast, the humidity can be measured from 20% to 90% humidity level, with the accuracy of ±1oC and ±1%. Data from the sensor is then sent to the ESP8266, which sends data to the webserver and finally to the user through the user interface. This process is programmed by using Arduino IDE. Next, through the user interface, the user can also switch on or off the light in the room remotely as long as the user is connected to the internet. The user can request data from the ESP8266, and the ESP8266 will turn the light on or off depending on the user. Generally, the user will be able to monitor the temperature and humidity in the room and control the light no matter where the user is, given both ESP8266 and the user are exposed to an internet connection.